2002
DOI: 10.1111/1467-9930.00134
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Adoption: Child Rights in the Brazilian Setting

Abstract: This paper, centered on adoption policy in Brazil, asks to what extent the open–ended principles apparent in international child rights accords, filtered down through different national laws, adjust to local realities. Ethnographic data on child circulation practices in urban favelas is compared with specific clauses in the 1990 Brazilian Children’s Code, as well as with adoption policies in North America, to question the code’s way of legislating which children can be placed for adoption, on what terms they s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
0
17
0
4
Order By: Relevance
“…Further in many cases, adoption is related to the stigma of single motherhood, and thus adopted children do not necessarily come from the lowest social stratum of the Korean society [29]. In contrast, studies on Columbia [30] and Brazil [31] have suggested that in these countries adoption is usually related to poverty and the care provided by adoption agencies is not always at the optimal level. Little is known on adoptions from other countries, but is likely that, for example, children adopted from Somalia and the Indian subcontinent have in many cases suffered from severe environmental stress before adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Further in many cases, adoption is related to the stigma of single motherhood, and thus adopted children do not necessarily come from the lowest social stratum of the Korean society [29]. In contrast, studies on Columbia [30] and Brazil [31] have suggested that in these countries adoption is usually related to poverty and the care provided by adoption agencies is not always at the optimal level. Little is known on adoptions from other countries, but is likely that, for example, children adopted from Somalia and the Indian subcontinent have in many cases suffered from severe environmental stress before adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Through this practice, documented by historians and social scientists in diverse parts of Brazil, parents will divide the economic onus and socializing responsibility involved in raising a child with a series of informally chosen foster families (Fonseca, 2002).…”
Section: Historical and Cultural Notes On Adoption And Foster Care Inmentioning
confidence: 99%
“…They may leave home because of a crisis-when their parents split up or pass through a period of particular financial difficulty-or for more banal reasons (the foster mother lives closer to a school or is an older person wanting company, etc.) (Fonseca, 2002).…”
Section: Historical and Cultural Notes On Adoption And Foster Care Inmentioning
confidence: 99%
See 1 more Smart Citation
“…São casos em que a criança se encontra em situações de adversidade e vulnerabilidade, por estar sujeita a maus tratos, negligência severa, drogadição ou alcoolismo de seus cuidadores, entre outras causas. Esse tipo de acolhimento relaciona-se ao processo de circulação de crianças, relatado por Fonseca (1995Fonseca ( , 2002 através de vários casos em que crianças passavam parte da infância ou juventude em casas que não eram a de seus genitores. Dentro do grupo de parentesco, ou até mesmo fora da rede consanguínea, existe uma coletivização das responsabilidades pelas crianças e ocorrem rearranjos para garantir subsídio financeiro e cuidado das mesmas.…”
unclassified